Understanding chronic disease risk factors and multimorbidity - Shakoori, Irfan Sharif; Aslam, Fauzia; Ashraf, Gohar; Akram, Hammad (International Journal Of Community Medicine And Public Health, 2020)
Chronic diseases and multimorbidity are becoming an alarming public health problem of this century. Multimorbidity is defined as “having two or more chronic diseases at one time in a person” and a result of complex biological, psychological and social phenomenon. The risks of multimorbidity can be divided into modifiable (behavioral factors) and non-modifiable (age, genetics) factors. Socioeconomic disadvantage and environmental factors can also influence on causation of it. Strategies aligned with primary, secondary and tertiary stages of prevention can help in the prevention of multimorbidity and reduction in complications among diseased. Multimorbidity requires multidimensional programs implemented through multiple stakeholder and policymaker’s collaboration.